Laísmo, leísmo and loísmo in six short stories by Juan Arzadun, Juan de Irigoyen, Miguel Aranaz and Rafael Sánchez - Goñi Alsúa, Edurne (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
Laísmo, leísmo and loísmo are three syntactic variations produced in Spanish, due to the incorrect use of the unstressed personal pronouns. These deviations of the linguistic norm have been widely studied from the synchronic, diachronic or functional points of view. Even, some scholars have traced back their origin to the dative case of Latin. Another possibility to study this topic is from the point of view of bilingualism and language contact. In this article, we are going to develop a textual study in which we will analyse the laísmo, leísmo and loísmo in six short stories written at the beginning of the 20th century, by fourwriters from Biscai –Juan Arzadun, Juan de Irigoyen, Manuel Aranaz Castellanos and Rafael Sánchez Mazas–, as a literary reflection of the use of the afore mentioned unstressed personal pronouns.
Keywords: Laísmo; leísmo; loísmo; short stories; Basque